THE EFFECT OF STUNTING ON EARLY CHILDHOOD LANGUAGE SKILLS - Sitti Zaifan; Sukiman; Andriyani; Trisni Herayati; Umilia; Ludgardis Wonga Wara; Yunaini (International Conferences on Early Childhood Education Proceedings, 2023)
Stunting is one of the growth problems that occur in children due to chronic malnutrition in the long term which will have an impact on inhibiting children's brain development including language skills. Children who are stunted can be seen from slow and short skeletal growth. According to data from the Indonesian Ministry of Health, the incidence of stunting in Jambi Province in 2018 was recorded at 30.2%. The purpose of this study was to analyze the effect of stunting on early childhood language skills in Limbur Lubuk Menguang District, Bungo Regency, Jambi Province. This type of research is a descriptive survey. The sample in this study was 107 children aged 3-5 years. The independent variable in this study is the incidence of stunting. The dependent variable is language progression. Data collection tools using observation sheets and KPSP (Pre-Screening Developmental Questionnaire). Research statistical tests use test-sign because the data is not homogeneous so that data analysis uses non-parametric statistics. The results showed a htest (0) < htable (2,7) with significance analysis (α) 0,05,  which concluded that the incidence of stunting affects the language development of children aged 3-5 years in Bungo district, Jambi Province. It is hoped that with this research, educators and parents can fulfill nutrition and apply parenting, so that lifestyle can minimize the risk of children suffering from stunting.